2019
DOI: 10.1002/job.2357
|View full text |Cite
|
Sign up to set email alerts
|

Are men better negotiators everywhere? A meta‐analysis of how gender differences in negotiation performance vary across cultures

Abstract: Summary Prior research has found that each culture and gender influences negotiation strategies and outcomes, but less is known about their interplay. We integrate these two research streams by providing a meta‐analytic review of the interactive impact of gender and culture on negotiation performance. We reviewed 185 studies that reported gender differences in intracultural negotiation performance across 30 societies that varied across seven cultural dimensions. Results showed that Hofstede's individualism–col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 112 publications
(157 reference statements)
0
25
0
1
Order By: Relevance
“…That there is substantial cross-cultural variation in gender differences in negotiation is confirmed by the meta-analysis ofShan et al (2019) 4. Gender inequality and poverty are particularly severe and intertwined in developing countries, such that tackling gender inequality has large potential to reduce poverty (World Bank 2012).…”
mentioning
confidence: 73%
“…That there is substantial cross-cultural variation in gender differences in negotiation is confirmed by the meta-analysis ofShan et al (2019) 4. Gender inequality and poverty are particularly severe and intertwined in developing countries, such that tackling gender inequality has large potential to reduce poverty (World Bank 2012).…”
mentioning
confidence: 73%
“…These findings question the widely accepted belief that men are better than women at negotiation by adding that it depends on several factors. Men are better negotiators in certain cultures, while women are superior in others (Shan et al, 2019;Shan et al, 2016). Many studies have dived deeper into identifying the specific differences that frame gender inequality in negotiations across different cultures.…”
Section: Gender Inequality In Negotiations Due To Cultural Differencesmentioning
confidence: 99%
“…After surveying Article: Research 117,000 IBM employees in 50 countries and 3 regions, Hofstede identified four cultural dimensions that shape organizations: individualism-collectivism (degree of group integration), power distance (extent of power inequality acceptance by the less powerful), uncertainty avoidance (tolerance for ambiguity), and masculinity-femininity (preference for heroism, assertiveness and material rewards over cooperation, caring for the weak and quality of life) (Hofstede, 1980). Although the masculinity-femininity category suggests a gender attribute, in 2019, a meta-analysis that examined 185 studies found that the strongest correlation between gender and measurable negotiation performance is flagged by the individualism-collectivism dimension (Shan et al, 2019). The meta-analysis found that men are more likely to outperform women in individualistic societies.…”
Section: Gender Inequality In Negotiations Due To Cultural Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that findings were often mixed (Stuhlmacher & Walters, 1999;Walters et al, 1998), and given that (psychological) research generally has long been characterized by low statistical power (Cohen, 1992;Maxwell, 2004), metaanalysis plays a crucial role in determining whether gender differences exist in behaviors and outcomes related to negotiations (see also Eagly & Wood, 2013). Meta-analyses revealed small yet significant gender differences, such that women as compared to men show less competitive negotiation behavior (Walters et al, 1998), obtain lower economic outcomes (Mazei et al, 2015;Shan et al, 2019;Stuhlmacher & Walters, 1999), and, of particular relevance for this commentary, are less likely to initiate negotiations (Kugler et al, 2018).…”
Section: Background In Briefmentioning
confidence: 99%